2015
DOI: 10.1155/2015/731434
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Omega-3 Polyunsaturated Fatty Acids in Gestational Diabetes: Consequences in Macrosomia and Adulthood Obesity

Abstract: Omega-3 polyunsaturated fatty acids (PUFAs) are increasingly being used to prevent cardiovascular diseases, including diabetes and obesity. In this paper, we report data on the observed effects of omega-3 PUFA on major metabolic disorders and immune system disruption during gestational diabetes and their consequences on macrosomia. While controversies still exist about omega-3 PUFA effects on antioxidant status regarding the level of omega-3 PUFA in diet supplementation, their lipid-lowering effects are unanim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 98 publications
(174 reference statements)
1
16
0
Order By: Relevance
“…Gestational diabetes mellitus and obesity during pregnancy are both complication which significantly influence the development of offspring during fetal life and postnatal. Diabetic pregnancy appears to induce macrosomia that results in obesity in adulthood and these pathologies are associated with several metabolic disorders, implicating lipid metabolism and altered antioxidant status [1]. Indeed, previous studies have shown that maternal diabetes in human and rat is associated with increased risk of hyperlipidaemia [2,3], metabolic syndrome and type 2 diabetes in the offspring [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Gestational diabetes mellitus and obesity during pregnancy are both complication which significantly influence the development of offspring during fetal life and postnatal. Diabetic pregnancy appears to induce macrosomia that results in obesity in adulthood and these pathologies are associated with several metabolic disorders, implicating lipid metabolism and altered antioxidant status [1]. Indeed, previous studies have shown that maternal diabetes in human and rat is associated with increased risk of hyperlipidaemia [2,3], metabolic syndrome and type 2 diabetes in the offspring [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…(2,3) HBW was closely related to childhood and adolescent obesity, which eventually leaded to the development of metabolic diseases in adulthood. (4,5) LBW may be a risk factor of chronic diseases, such as type 2 diabetes, osteoporosis, coronary heart disease, hypertension, and kidney disease in adulthood. (6) Low-grade inflammation during pregnancy was associated with premature birth, pre-eclampsia, gestational diabetes and LBW.…”
mentioning
confidence: 99%
“…This has been shown by several studies in past in different patient groups, including SC [6] and diabetes, [55] where they have been noted to induce amelioration of the symptoms and improve well-being [56]. Dietary DHA and EPA, after incorporation into the cell membrane, have also been shown in previous studies to increase membrane fluidity and thus affect the activity of the transmembrane proteins [12].…”
Section: Omega-3 Fatty Acidsmentioning
confidence: 76%